Chronic cough in cystic fibrosis: the effect of modulator therapy on objective 24-h cough monitoring. Issue 2 (3rd May 2022) - Zhang, Mengru; Brindle, Kayleigh; Robinson, Melanie; Ingram, Debbie; Cavany, Tanya; Morice, Alyn
Cystic fibrosis (CF) is an autosomal recessive condition, deletion of phenylalanine at position 508 (F508del) being the most frequent mutation in CF patients. Kaftrio, also called Trikafta in the USA, (Vertex Pharmaceuticals Inc., Germany) is a licensed modulator therapy for CF patients with at least one F508del mutation [1]. Several clinical trials have demonstrated its efficacy [2]. However, the primary outcome measured in these studies was the change in per cent predicted of forced expiratory volume in 1 s (FEV1 ), which was in the order of 10%, and thus may have a relatively low sensitivity in predicting efficacy, particularly in more severely affected patients [3]. This is a prospective observation of the effect of Kaftrio initiation in CF. An early and dramatic improvement in the objective measure of 24-h cough monitoring was observed, providing noninvasive, objective evidence of efficacy and compliance in CF. https://bit.ly/3LpnABB